The Implementation of Indonesia Accounting Principle SAK EMKM and PSAK 72 on Cv Smart Management - Kacaribu, Anton Adventus; Viorene (Poltanesa, 2022)
This paper aims to answer the problem formulation on applying and recognizing SAK EMKM and PSAK 72 revenue in micro CV Smart Management business. The qualitative research method used a literature study approach and content analysis. Financial data are collected directly from the first sources, and other data are gathered from direct interviews. The secondary data was gathered from many kinds of literature, such as sources from the Indonesia Accounting Association (IAI) in the form of SAK EMKM, specifically designed for micro and medium-sized companies and PSAK 72 regulations, and equipped with books and scientific research as a tertiary data. In this research, the researcher elaborates on a comparison of the Indonesia accounting principle SAK EMKM and PSAK 72 to its implementation on CV Smart Management. The results obtained are that CV Smart Management has implemented SAK EMKM based on accounting standards according to SAK EMKM and PSAK 72 with revenue recognition based on the five stages of the model in PSAK 72. From this research, it can be concluded the financial report are not complete. The company did not perform notes on the financial statement report. There is an inappropriate arrangement regarding the liquidity of accounts. In the implementation of PSAK 72, CV Smart Management has not allocated the obligations in details of obligation identification so it can impact the income recognition.